The potential of bioactives as biosensors for detection of pH. Issue 1 (March 2020) - Wulandari, Anting; Sunarti, Titi Candra; Fahma, Farah; Enomae, Toshiharu
Abstract: In the field of food safety, pH measurement is very important because pH can be an indicator of freshness of a food product. In general, the pH measurement is performed using a sensor from synthetic chemicals. The use of chemicals as pH sensors has several disadvantages that are toxic and threaten human health. Therefore, pH biosensors should be developed from bioactive compound. Bioactives such as curcumin, anthocyanin, chlorophyll, and Angkak pigments are indigeneous natural resources that produce color with specific specificity. Curcumin was extracted from turmeric ( Curcuma longa L.), anthocyanin from purple sweet potato ( Ipomoea batatas L), chlorophyll from suji leaf ( Pleomele angustifolia ), and reddish pigment from rice fermented by Monascus sp. The type of color of each bioactive can give different responses to certain pH so that it is potential to be developed as a pH biosensor. However, bioactives have sensitivity to certain pH, so it is necessary to test the sensitivity and selection of bioactives to various pH (2-'3). The results of the sensitivity of the bioactives to pH 2-'3 showed that anthocyanin and curcumin were the best bioactive as pH biosensor because they provide a unique and significant color change compared to angkak pigment and chlorophyll which did not show clear discoloration. The anthocyanin was sensitive to pH 5-13 and curcumin was sensitive to pH 7-13 and both were stable at acidic pH.